Emerging Stacked Photocatalyst Design Enables Spatially Separated Ni(OH)2 Redox Cocatalysts for Overall CO2 Reduction and H2O Oxidation. Issue 9 (16th December 2021) - Liu, Qian; Wang, Shihong; Mo, Weihao; Zheng, Yiyi; Xu, Yanbo; Yang, Guodong; Zhong, Shuxian; Ma, Jun; Liu, Dong; Bai, Song
Abstract: Construction of photocatalytic systems with spatially separated dual cocatalysts is considered as a promising route to modulate charge separation/transfer, promote surface redox reactivities, and prevent unwanted reverse reactions. However, past efforts on the loading of spatially separated double‐cocatalysts are limited to hollow structured semiconductors with inner/outer surface and monocrystalline semiconductors with different exposed facets. To overcome this limitation, herein, enabled by a unique stacked photocatalyst design, a facile and versatile strategy for spatial separation of redox cocatalysts on various semiconductors without structural and morphological restriction is demonstrated. The smart design begins with the deposition of light‐harvesting semiconductors on reduced graphene oxide (rGO) nanosheets, followed with the coverage of Ni(OH)2 outer layer. The ternary photocatalysts exhibit superior activities and stabilities of H2 O oxidation and selective CO2 ‐to‐CO reduction, remarkably surpassing other counterparts. The origin of the enhanced performance is attributed to the synergistic interplay of rGO@Ni(OH)2 reduction cocatalysts surrounding the semiconductors and Ni(OH)2 oxidation cocatalysts directly supported by the semiconductors, which mitigates the charge recombination, supplies highly active and selective sites for overall reactions, and preserves the semiconductors from photocorrosion. This work presents a new approach to regulating the position of dual cocatalysts and ameliorating the net efficiency of photoredox catalysis. Abstract : A versatile strategy is developed based on a smart stacked photocatalyst design, which allows the spatially separated Ni(OH)2 redox cocatalysts on various light‐harvesting semiconductors without structural and morphological limitation. The synergy of rGO@Ni(OH)2 reduction cocatalyst surrounding the semiconductor and Ni(OH)2 oxidation cocatalyst directly supported by the semiconductor enables the CO2 ‐to‐CO/O2 conversion with remarkable activity, selectivity, and stability.